Cold stress tolerance during early growth stages of naturalized Helianthus petiolaris populations - Gutierrez, Agustina; Cantamutto, Miguel Angel; Poverene, Maria Monica (2018)
In the last 10 years the sunflower crop area of Argentina has shifted towards the Southwest as a result of the expansion of soybean cultivation. Early sowings require greater tolerance to low temperatures in order to optimize the use of water resources by the crop, especially in the seedling stage, when cold stress limits growth and productivity. Helianthus petiolaris is a wild genetic resource that has contributed to the production of sunflower cultivars. The goal of this study was to evaluate the tolerance to low temperatures in H. petiolaris plants. Morphological traits (plant height, leaf width and leaf length) and physiological traits (electrolyte leakage, chlorophyll content, and glucose content) were compared in eight accessions having an early germination in the field and one with normal life cycle. Acclimated and non-acclimated plants were subjected to cold stress followed by a recovery period. Physiological traits during early growth stages showed differences in cold tolerance and for acclimation ability between accessions, suggesting the existence of heritable components. Four accessions were the most cold-tolerant among the studied populations, suggesting a natural adaptation related to the geographical site. Results point out that H. petiolaris is a useful genetic resource to contribute to sunflower breeding in the search of cold tolerant cultivars.